Strategi Pengembangan Sektor Pertanian Di Desa Tlontoraja, Kabupaten Pamekasan - Novia Faradilla Basmalah; Elys Fauziyah; Amanatuz Zuhriyah (Agriculture Faculty of Flores University, 2023)
Tlontoraja Village has the biggest potential in the agricultural sector, this is strengthened by the large number of people working in the agricultural sector, namely 5.076 residents. However, the agricultural sector in the village is still not able to provide a good enough contribution because of the various problems it faces, both originating from the internal and external conditions of the village. This study used eight informants consisting of three lecturers from the Islamic University of Madura, staff of agricultural institutions, heads of agricultural extension officers, heads of villages, heads of Gapoktan, and heads of farmer groups. The data obtained were analyzed using the IFAS matrix, EFAS, and the SWOT matrix. The results showed that there were nine supporting factors and fife inhibiting factors in the agricultural development of Tlontoraja Village. In addition, the internal factor that has the highest score is Tlontoraja Village having a BUMDes institution and an agricultural extension agency as a companion in agricultural sector activities, and for external factors, the highest score is that there is a national development plan in Tlontoraja Village. The strategies that are prioritized and can be implemented are the use of modern technology in cooperation activities, there is a performance collaboration between farmer group leaders and educational institutions, there is broad marketing access inside and outside the village, and farmers and BUMDes institutions can collaborate to seek more efficient and profitable crop marketing network.